A Valid Bisphosphonate Modified Calcium Phosphate-Based Gene Delivery System: Increased Stability and Enhanced Transfection Efficiency In Vitro and In Vivo - Ming Zhao; Ji Li; Dawei Chen; Haiyang Hu (MDPI AG, 2019)
Calcium phosphate (CaP) nanoparticles, as a promising vehicle for gene delivery, have been widely used owing to their biocompatibility, biodegradability and adsorptive capacity for nucleic acids. Unfortunately, their utility in vivo has been profoundly restricted due to numerous technical barriers such as the lack of tissue specificity and limited transfection efficiency, as well as uncontrollable aggregation over time. To address these issues, an effective conjugate folate-polyethylene glycol-pamidronate (shortened as FA-PEG-Pam) was designed and coated on the surface of CaP/NLS/pDNA (CaP/NDs), forming a versatile gene carrier FA-PEG-Pam/CaP/NDs. Inclusion of FA-PEG-Pam significantly reduced the size of CaP nanoparticles, thus inhibiting the aggregation of CaP nanoparticles. FA-PEG-Pam/CaP/NDs showed better cellular uptake than mPEG-Pam/CaP/NDs, which could be attributed to the high-affinity interactions between FA and highly expressed FR. Meanwhile, FA-PEG-Pam/CaP/NDs had low cytotoxicity and desired effect on inducing apoptosis (71.1%). Furthermore, FA-PEG-Pam/CaP/NDs showed admirable transfection efficiency (63.5%) due to the presence of NLS peptides. What’s more, in vivo studies revealed that the hybrid nanoparticles had supreme antitumor activity (IR% = 58.7%) among the whole preparations. Altogether, FA-PEG-Pam/CaP/NDs was expected to be a hopeful strategy for gene delivery.